Pengaruh Subsidi Energi dan Konsumsi Listrik terhadap Pertumbuhan Ekonomi di Indonesia - Ulkya Maisarah; Muhayratu Farisha; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to see the effect between energy subsidies and electricity consumption on economic growth in Indonesia. This study uses secondary time series data for the period 2014-2023 with a quantitative approach using the Eviews 12 software analysis tool. The variables in this study are energy subsidies, electricity consumption and economic growth which are analyzed by multiple linear regression methods. The results showed that energy subsidies have a positive and insignificant effect on economic growth, electricity consumption has a positive and significant effect on economic growth in Indonesia. While energy subsidies and electricity consumption simultaneously have no significant effect on economic growth in Indonesia in the 2014-2023 period.